Rekrutmen Caleg DPRD Sumut dalam Partai Nasdem Tahun 2014 - KAFI GEUMALA RAMPAN H. (Universitas Sumatera Utara, 2015)
Election is an embodiment of the passage of democratic political life. Election is also a benchmark for democracy because it involves the direct participation of the people in determining political leaders. This study is about North Sumatera legislatif candidates recruit-ment process in Nasdem Party at 2014. The focus is to discuss about what are the step in North Sumatera legislatif candidates recruitment mechanism in Nasdem Party. The findings of this study include there are four step in North Sumatera legislatif candidates recruitment mechan-ism. First, the formation of legislative candidating team work; Second, the legislative candidate registration; Third, legislative candidating verification; Fourth, the determining and inquiry of legislative candidate to the centre party. The method used is descriptive-qualitative method. This study is using political institutional as the approach and the data collection is using field research.Keywords: Political recruitment, legislative candidate, candidate selection.